The Effectiveness of Behavioral Counseling with Modeling Techniques to Improve Self-Succorance through Lesson Study - Komang Teja Budiarta; I Ketut Dharsana; Ni Ketut Suarni (Bisma The Journal of Counseling, 2018)
This study aims to determine the effectiveness of behavioral counseling with modeling techniques to improve self-succorance through lesson study for eighth grade students of SMP Negeri 2 Singaraja. Experimental research uses pretest-posttest Control Group Design. The population of this research is VIII grade students of SMP Negeri 2 Singaraja. The study sample was 60 students. Through random sampling techniques, 30 students were placed in the experimental group class VIII.4 and 30 students constituted the control group in class VIII.9. The data of this study were analyzed by independent sample t-test using JASP software version 0.10.0.0 and D'Cohen to determine the level of effectiveness. The results obtained t = 14,921, p <0.05, Effect Size (ES) examiners showed high effectiveness = (ES 3,853), these results prove behavioral counseling with effective modeling techniques to improve the self-succorance of VIII.4 grade students of SMP Negeri 2 Singaraja For this reason BK teachers can use behavioral counseling with modeling techniques to improve self-succorance in class VIII students of SMP Negeri 2 Singaraja.